BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM BREAD MAKING POSSIBILITY OF ALGERIAN DURUM WHEAT WHEAT - A., Kirouani 1,2*2*; M., . Taghouti 3; L., Boukhalfoun (university of eloued جامعة الوادي, 2020)
Actually, gluten strenght, yel Actually, gluten strenght, yel Actually, gluten strenght, yel Actually, gluten strenght, yel Actually, gluten strenght, yelActually, gluten strenght, yel Actually, gluten strenght, yel Actually, gluten strenght, yel Actually, gluten strenght, yel Actually, gluten strenght, yel Actually, gluten strenght, yellow pigment content and protein low pigment content and protein low pigment content and proteinlow pigment content and protein low pigment content and proteinlow pigment content and protein low pigment content and protein low pigment content and proteinlow pigment content and protein low pigment content and protein low pigment content and proteinlow pigment content and protein quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in quality paly an axial role in durum wheat durum wheat durum wheat durum wheat selectionselectionselection selection selection . I . In order to characterize the baking quality n order to characterize the baking quality n order to characterize the baking quality n order to characterize the baking quality n order to characterize the baking qualityn order to characterize the baking quality n order to characterize the baking qualityn order to characterize the baking qualityn order to characterize the baking qualityn order to characterize the baking quality n order to characterize the baking quality n order to characterize the baking qualityn order to characterize the baking qualityn order to characterize the baking quality n order to characterize the baking qualityn order to characterize the baking qualityn order to characterize the baking quality n order to characterize the baking quality n order to characterize the baking quality n order to characterize the baking quality n order to characterize the baking quality of Al of Al geri gerigerian germplasm, an germplasm, an germplasm, an germplasm, an germplasm, we we we used used eighteen (18eighteen (18 eighteen (18eighteen (18eighteen (18 eighteen (18 ) local and ) local and ) local and ) local and ) local and improved improved improved durum wheat durum wheat durum wheatdurum wheats cultivars. cultivars. cultivars. cultivars. The present study showed the The present study showed the The present study showed the The present study showed the The present study showed the The present study showed the The present study showed the The present study showed the The present study showed the The present study showed the The present study showed the presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS presence of significant differences within our genetic resources for several traits. SDS sedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidisedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidisedimentation test results suggested that, Ofanto, Bidi sedimentation test results suggested that, Ofanto, Bidisedimentation test results suggested that, Ofanto, Bidisedimentation test results suggested that, Ofanto, Bidi 17 , Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in Mexicali, Saoura were classified in the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten the same rank as Marzak, which are considered best cultivars, with a very high gluten strength and a strength and a strength and a strength and a strength and a strength and a top score top score top score (8) revealed by a mixoragraphy test revealed by a mixoragraphy testrevealed by a mixoragraphy testrevealed by a mixoragraphy testrevealed by a mixoragraphy test revealed by a mixoragraphy test revealed by a mixoragraphy testrevealed by a mixoragraphy testrevealed by a mixoragraphy test revealed by a mixoragraphy test revealed by a mixoragraphy testrevealed by a mixoragraphy test revealed by a mixoragraphy test revealed by a mixoragraphy test , these , these , these varieties are important for varieties are important for varieties are important for varieties are important for varieties are important for varieties are important for varieties are important for varieties are important for varieties are important for varieties are important for varieties are important for varieties are important for varieties are important for varieties are important for bread making bread makingbread making bread making . Yellow pigments . Yellow pigments . Yellow pigments . Yellow pigments . Yellow pigments . Yellow pigments . Yellow pigments . Yellow pigments analanal analysis showed that, Saoura, Oued Elb ysis showed that, Saoura, Oued Elbysis showed that, Saoura, Oued Elb ysis showed that, Saoura, Oued Elbysis showed that, Saoura, Oued Elb ysis showed that, Saoura, Oued Elb ysis showed that, Saoura, Oued Elbysis showed that, Saoura, Oued Elbysis showed that, Saoura, Oued Elb ysis showed that, Saoura, Oued Elb ysis showed that, Saoura, Oued Elb ysis showed that, Saoura, Oued Elb ysis showed that, Saoura, Oued Elb ared and Waha ared and Waha ared and Waha ared and Waha ared and Waha ared and Waha ared and Waha ared and Waha ared and Waha ared and Waha presented a high presented a high presented a high presented a highpresented a highpresented a high yellow pigmen yellow pigmen yellow pigmen yellow pigmenyellow pigmen yellow pigmenyellow pigment content than the check Louiza t content than the check Louizat content than the check Louiza t content than the check Louiza t content than the check Louizat content than the check Louiza t content than the check Louizat content than the check Louizat content than the check Louiza t content than the check Louizat content than the check Louiza t content than the check Louiza t content than the check Louiza known for its high yellow known for its high yellow known for its high yellow known for its high yellow known for its high yellow known for its high yellow known for its high yellow known for its high yellow known for its high yellow known for its high yellow known for its high yellow known for its high yellow index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program.index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program.index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program.index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program.index. These results are very motivating to be used in Algerian selection program.index. These results are very motivating to be used in Algerian selection program.index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program. index. These results are very motivating to be used in Algerian selection program.index. These results are very motivating to be used in Algerian selection program. index.
artical
Keywords: index. These results are very motivating to be used in Algerian selection program. Keywords: Keywords: Keywords:Keywords: durum wheat durum wheat durum wheatdurum wheat; yellow yellow yellow pig ment s; mixograph mixograph mixograph mixograph ; gluten strength gluten strengthgluten strength gluten strength gluten strength ; bread making. bread making.bread making.bread